2017
DOI: 10.1111/sms.12837
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of leisure‐time sport activities in adolescence as a predictor of leisure‐time physical activity in adulthood

Abstract: Because sustained physical activity is important for a healthy life, this paper examined whether a greater diversity of sport activities during adolescence predicts higher levels of leisure-time physical activity (LTPA) in adulthood. From sport activity participation reported by 17-year-old twins, we formed five groups: 1, 2, 3, 4, and 5+ different sport activities. At follow-up in their mid-thirties, twins were divided into four activity classes based on LTPA, including active commuting. Multinomial regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 40 publications
3
37
2
Order By: Relevance
“…50,51 Therefore, encouraging maintenance of OPA throughout adolescence may be important because sport participation at younger ages predicts later leisure time PA levels. 44,52 Consistent with most literature, 53,54 the likelihood of sport nonparticipation increased with increasing age. Also, consistent with researchers suggesting that performance sport participation is not accessible to all given its cost, 7,14,21 low household income was associated with a lower probability of performance sport participation in our study.…”
Section: Discussionsupporting
confidence: 82%
“…50,51 Therefore, encouraging maintenance of OPA throughout adolescence may be important because sport participation at younger ages predicts later leisure time PA levels. 44,52 Consistent with most literature, 53,54 the likelihood of sport nonparticipation increased with increasing age. Also, consistent with researchers suggesting that performance sport participation is not accessible to all given its cost, 7,14,21 low household income was associated with a lower probability of performance sport participation in our study.…”
Section: Discussionsupporting
confidence: 82%
“…An important component of LTPA is sport, a term which in the Australian context is usually reserved for competitive activities undertaken in community club settings (Eime et al, 2013a). Participation in organized sport makes an important contribution to overall LTPA levels across the lifespan (Olds et al, 2009;Makela et al, 2017). Furthermore, there is evidence that participation in club-based and particularly team-based sport can be associated with better psychosocial health than individual activities, due to the social nature of participation (Eime et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…There are recent researches in relation to the identification of patterns of physical activities which are positive for health [3]. More specifically, some recent studies have shown the association between habits of physical activity in young people and being physically active in adulthood [4,5]. Moreover, it…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is of utmost importance to examine behaviours linked to health, with the main aim of explaining the current situation in society. So, the attention must be focused on some stages such as adolescence and youth, as they are essential in the acquisition of future healthy lifestyles [4]. Regarding gender, women practice less physical activity, and this inactivity increases with age [9,10].The activities developed during free time are associated with fun, satisfaction and pleasure.…”
mentioning
confidence: 99%